On the dual roles and polarized phenotypes of neutrophils in tumor development and progression. - Piccard, H; Muschel, R; Opdenakker, G (2012)
Inconsistencies plague our understanding of the role of neutrophils in cancer and the literature provides evidence for a duality in neutrophil activity on the outcome of cancer. Here, the different effects of neutrophils during the multiple subprocesses of cancer development and progression are overviewed, in order to gain insight into the features of both antitumoral and protumoral tumor-associated neutrophils (TAN). Neutrophils can counteract the progression of malignancies through tumor cytotoxicity, tumor rejection and enhancement of antitumoral immune memory. These cells have recently been phenotypically denominated N1 neutrophils. Recent studies indicate that cytokines, such as TGF-β and IFN-β, are involved in directing neutrophil polarization by the tumor microenvironment. With the opposite polarity, N2 neutrophils may be detrimental for the host and beneficial for tumor growth, invasion and metastasis, e.g. through proteolysis of extracellullar matrix components, promotion of angiogenesis and mediation of immunosuppression.